Evaluation of behaviors concerning preparation home meals - Kozłowski, Piotr; Kozłowska, Magdalena; Kozłowska, Karolina (Journal of Education, Health and Sport, 2017)
The aim of the study was to evaluate the behavior and habits of preparing meals at home. The study included 254 participants. In the study group, 55,5% of respondents were females whereas 45,5% were males. The age of participants ranged from 20 to 60 years. The study conducted in the period from Mary 2016 to January 2017 and it employedstandardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 21 questions single-choice questions. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. Respondents were asked about education, hygiene knowledge, domestic food preparation experience, hygiene practice, food handling rules and food poisoning at home and among immediate family members. The questionnaire contained a number of questions about how participants keep food at home. On the question of food security leak in a refrigerator (suitable storage containers, food foil etc.), the majority of respondents indicated that it is important for them (65.7%), more female chose this answer. While for the remaining 34.3% of respondents did not matter much. Only 31.1% of respondents separately store in the fridge fruits and vegetables. 92,9% of respondents do not freeze again the previously thawed food. Only 7.1% of respondents said that they freeze meals again and do not care about the consequences.66.5% of respondents regularly checks the expiration date of stored food in the house. More than 94% of respondents admitted that they had eaten over-the-counter food at least several times, but only 6.3% of them had gastrointestinal symptoms.Consumption of overdue foods at least once a month is declared by 33.1% of respondents, they were mostly male and people living in small cities.